(untitled) (Nigerian Journal of Technology, 2015)
The performance of peer-to-peer systems is based on the quality and quantity of resource contributions from participating peers. In most systems, users are assumed to be cooperative, but in reality, sharing in peer-to-peer systems is faced with the problem of free riding. In this paper, we model the interactions between peers as a modified gift giving game and proposed an utility exchange incentive mechanism to inhibit free riding. This technique allows peers to either upload or download resources based on their best strategy and interest. Through extensive simulations, we show that this mechanism can increase fairness and encourage resource contribution by peers to the network. This will ensure a resourceful and stable peer- to-peer systems. http://dx.doi.org/10.4314/njt.v34i2.23